Pathogen-Associated Molecules from Gut Translocation Enhance Severity of Cecal Ligation and Puncture Sepsis in Iron-Overload β-Thalassemia Mice - Sae-khow K; Charoensappakit A; Visitchanakun P; Saisorn W; Svasti S; Fucharoen S; Leelahavanichkul A (Journal of Inflammation Research, 2020)
Kritsanawan Sae-khow,1 Awirut Charoensappakit,2 Peerapat Visitchanakun,1 Wilasinee Saisorn,2 Saovaros Svasti,3 Suthat Fucharoen,3 Asada Leelahavanichkul2,4 1Medical Microbiology, Interdisciplinary and International Program, Graduate School, Chulalongkorn University, Bangkok, Thailand; 2Translational Research in Inflammation and Immunology Research Unit (TRIRU), Department of Microbiology, Chulalongkorn University, Bangkok, Thailand; 3Thalassemia Research Center, Institute of Molecular Biosciences, Mahidol University, Nakornpathom, Thailand; 4Department of Microbiology, Faculty of Medicine, Chulalongkorn University, Bangkok, ThailandCorrespondence: Asada LeelahavanichkulTranslational Research in Inflammation and Immunology Research Unit (TRIRU), Department of Microbiology, Chulalongkorn University, Bangkok 10330, ThailandTel +66-2-256-4251Fax +66-2-252-6920Email aleelahavanit@gmail.comIntroduction: Systemic inflammation induced by gut translocation of lipopolysaccharide (LPS), a major component of Gram-negative bacteria, in thalassemia with iron-overload worsens sepsis. However, the impact of (1→ 3)-β-D-glucan (BG), a major fungal molecule, in iron-overload thalassemia is still unclear. Hence, the influence of BG was explored in 1) iron-overload mice with sepsis induced by cecal ligation and puncture (CLP) surgery; and 2) in bone marrow-derived macrophages (BMMs).Methods: The heterozygous β-globin-deficient mice, Hbbth3/+ mice, were used as representative thalassemia (TH) mice. Iron overload was generated by 6 months of oral iron administration before CLP surgery- induced sepsis in TH mice and wild-type (WT) mice. Additionally, BMMs from both mouse strains were used to explore the impact of BG.Results: Without sepsis, iron-overload TH mice demonstrated more severe intestinal mucosal injury (gut leakage) with higher LPS and BG in serum, from gut translocation, when compared with WT mice. With CLP in iron-overload mice, sepsis severity in TH mice was more severe than WT as determined by survival analysis, organ injury (kidney and liver), bacteremia, endotoxemia, gut leakage (FITC-dextran) and serum BG. Activation by LPS plus BG (LPS+BG) in BMMs and in peripheral blood-derived neutrophils (both WT and TH cells) demonstrated more prominent cytokine production when compared with LPS activation alone. In parallel, LPS+BG also prominently induced genes expression of M1 macrophage polarization (iNOS, TNF-α and IL-1β) in both WT and TH cells in comparison with LPS activation alone. In addition, LPS+BG activated macrophage cytokine production was enhanced by a high dose of ferric ion (800 mM), more predominantly in TH macrophages compared with WT cells. Moreover, LPS+BG induced higher glycolysis activity with similar respiratory capacity in RAW264.7 (a macrophage cell line) compared with LPS activation alone. These data support an additive pro-inflammatory effect of BG upon LPS.Conclusion: The enhanced-severity of sepsis in iron-overload TH mice was due to 1) increased LPS and BG in serum from iron-induced gut-mucosal injury; and 2) the pro-inflammatory amplification by ferric ion on LPS+BG activation.Keywords: thalassemia, iron overload, leaky-gut, sepsis